Idioms of distress : psychosomatic disorders in medical and imaginative literature - Furst, Lilian R. (State University of New York Press, 2003)
"This interdisciplinary study examines the enigmatic category of psychosomatic disorders as articulated in medical writings and represented in literary works of the nineteenth and twentieth centuries. Six key works are analyzed: Hawthorne's The Scarlet Letter, Emile Zola's Therese Raquin, Thomas Mann's Buddenbrooks, Arthur Miller's Broken Glass, Brian O'Doherty's The Strange Case of Mademoiselle P., and Pat Barker's Regeneration. Each is a case study in detection as the hidden sources of bodily ills are uncovered in intra- or interpersonal conflicts such as guilt, family tensions, and marital discord. The book fosters a better understanding of these puzzling disorders by revealing how they function simultaneously as masks and as manifestations of inner suffering."--Jacket